THE RESPONSE OF TWO POTATO CULTIVARS TO ORGANIC AND BIO FERTILIZATION AND THEIR INTERACTION WITH CHEMICAL FERTILIZATION ON SOME GROWTH AND YIELD TRAITS - AL-Shmary , Rusul F.; AL-Taey, Duraid K.A. (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted in a field of potato farmers in Babylon province, Al-Dabla region south of Al-Hilla city during the autumn season (2018-2019). This study aimed to study two factors: First factor: the cultivars (Riviera and Arizona) class A resulting from cultivation of class E imported and cultivated in spring season 2018. The second factor: the effect of fertilizer combinations, the Arizona cultivar was significantly excelled in most of the measured traits compared to the Rivera cultivar. Significant differences were observed between the treatments of fertilizer combinations, Where the treatment (organic fertilizer + bio-fertilizer + 25% chemical fertilizer) was significantly excelled compared to the control treatment in the study indicators. Bi-interaction treatment (Arizona cultivar + organic fertilizer + bio-fertilizer + chemical fertilizer 25%) achieved the highest values for the number of Aerial stems amounted to (3.374 stems.plant-1) and the total yield for tubers (43.24 tons.ha-1).